Volumetric properties of stone mastic asphalt mixture incorporated with nano silica and glass fiber - Abdullah Baqadeem, Abdullah Omar; Khairil Azman, Masri; Mazlan, Abu Seman; Muzamir, Hasan; Che Puan, Othman; Putra Jaya, Ramadhansyah (Suranaree University of Technology, 2025)
Stone Mastic Asphalt (SMA) has become integral to contemporary road construction due to its exceptional durability and performance. The stability of SMA, a key determinant of its resistance to deformation under diverse traffic and environmental conditions, underscores its effectiveness. Moreover, the flow characteristics of SMA play a pivotal role in its workability and compaction during construction. This study aims to evaluate the impact of nano silica-modified bitumen on rheological properties, encompassing viscosity, penetration, and softening point. Additionally, the research investigates the influence of glass fiber reinforcement on the mechanical properties of the asphalt mixture, explicitly focusing on volumetric properties and the Marshall stability test. In pursuit of these objectives, pure bitumen underwent modification with (1-5%) nano silica using a high-shear mechanical mixer, and (0, 0.2, 0.4, 0.6, 0.8, and 1%) glass fiber was incorporated into the asphalt mixture. The findings reveal that the asphalt mixture exhibits enhanced Marshall stability, stiffness, and flow values compared to conventional asphalt mixtures. Notably, the modified bitumen containing 4% nano silica and the hybrid asphalt mixture with a 0.4% glass fiber concentration demonstrate the most significant improvements in Marshall stability. The study establishes a positive correlation between the addition of nano silica to bitumen and glass fiber to the asphalt mixture, indicating a beneficial impact on the overall mechanical characteristics of the pavement.